Medical staff evaluation on ‘the effect of medical alliance policy on hierarchical diagnosis and treatment’ - Zhao, Zijun; Xie, Xianyu; Wu, Qinde (Frontiers in Public Health, 2024)
Introduction Medical alliances are essential for constructing an hierarchical diagnosis and treatment (HDT) system; therefore, it is crucial to promote such alliances and evaluate their effectiveness in this regard from the medical staff perspective. This study thus investigated and analyzed the evaluations of medical staff in China concerning the effect of medical alliances on promoting HDT with the intention to encourage further establishment of medical alliances and HDT under China’s new medical reform. Methods A total of 616 medical staff personnel from 3 medical alliances in Fujian Province were surveyed, and data were analyzed using SPSS 20.0 software. Results The level of medical institutions, posts and satisfaction with their medical alliances influenced the evaluation of medical alliance effectiveness in resolving the problem of expensive medical services. Primary medical institutions are more inclined toward policy formulation and related work; thus, the interests of primary hospitals can be guaranteed. However, tertiary hospitals must provide additional workforce, material, and financial resources to support primary hospitals. Discussion Therefore, it is necessary to coordinate the interests of the medical staff at different levels of medical institutions. The study makes a significant contribution to the literature because it highlights the effect of medical alliances in promoting hierarchical diagnosis and treatment.